ENVIRONMENTAL EFFECTS AND THEIR COSTS IN THE TRANSITION TOWARDS ACADEMIC VIRTUALITY (Costos y Gestión, 2020)
Global trends such as the sustainability of organizational practices, adherence to international standardsand waste reduction are perceived in the demands of society through legislative pressure and the demandfor information transparency on responsible actions with the environment and in accordance with interestsof your interest groups. Aware of the importance of reducing the impact of activities on the environmentand competing in a globalized environment that requires sustainability protocols, our country’s organizationshave begun to inventory greenhouse gases by quantifying the emission sources for development of the lifecycle of goods together with the natural and energy resources used for it.The purpose of our work is to determine the environmental effects of the adoption of the distance modalityin the degree courses of an Argentine public management university in order to verify the reduction that ismade on the emission of greenhouse gases -GHG - and the decrease in transportation costs correspondingto students. The results show a significant saving in the indirect effects of GHG, such as student mobility andtransportation costs, while for direct effects, savings are concentrated in the reduction of energy consumption of luminaires and computer equipment.
Keywords: Virtualization; Social responsibility; Carbon footprint; Costs; Sustainable development